Longitudinal change of serum NfL as disease activity biomarker candidate in MOGAD: a descriptive cohort study - Schindler, Patrick; Bellmann-Strobl, Judith; Kuhle, Jens; Wildemann, Brigitte; Jarius, Sven; Paul, Friedemann; Ruprecht, Klemens (Multiple Sclerosis and Related Disorders, 2024)
Background - Myelin oligodendrocyte glycoprotein antibody (MOG-IgG)-associated disease (MOGAD) is an autoinflammatory disease of the central nervous system. MOGAD often follows a relapsing course that can lead to severe disability, but monophasic disease is possible as well. Currently, there is an unmet clinical need for disease activity biomarkers in MOGAD. Serum neurofilament light chain (sNfL) is a sensitive biomarker for neuroaxonal damage. However, data on longitudinal change of sNfL as disease activity biomarker for MOGAD are scarce. - Objective - To describe the longitudinal course of sNfL in adult patients with MOGAD in an active as well as a stable disease state in relation to clinical parameters and serum MOG-IgG titers. - Methods - We conducted a retrospective, exploratory, monocentric cohort study of adult patients with MOGAD. Cohort 1 consisted of five patients in whom NfL was tested as part of their routine clinical workup, all of which had active disease (maximum 6 months since last attack, median 3 months). Cohort 2 comprised 13 patients, which were tested for NfL in the context of a longitudinal study at predefined time intervals, mostly during remission (median 10 months since last attack). sNfL was measured using single molecule array (Simoa) technology at least at two time points (median 3) within a median observation time of 5 months in cohort 1, and at baseline and after a median duration of 12 months in cohort 2. MOG-IgG titers were measured by a fixed cell-based assay. - Results - Change in sNfL correlated positively with change in MOG-IgG titers (rho=0.59, p = 0.027). The variability of sNfL (difference between highest and lowest level) during the observation period was higher in patients who had an attack within six months before baseline (median 37 [interquartile range [IQR] 10-64] pg/ml vs. 2.3 [IQR 1-5] pg/ml, p = 0.006). sNfL increased in patients with an attack during the observation period. Patients with baseline sNfL measurement within two weeks after attack symptom onset displayed relatively low initial sNfL with an increase afterwards. - Conclusions - Longitudinal sNfL change correlates with MOG-IgG titer change and may be a promising biomarker candidate for disease activity in MOGAD. Increasing sNfL levels might be utilized to adjudicate suspected attacks. In acute attacks, sNfL increase may occur with a delay after symptom onset.